Effectiveness of the fixed-dose combination therapy with perindopril and amlodipine in coronary heart disease patients after coronary artery bypass graft surgery - B. G. Iskenderov; O. N. Sisina; O. A. Kameneva (Кардиоваскулярная терапия и профилактика)
Aim. To study the effectiveness of the fixed-dose combination therapy with perindopril and amlodipine (Prestance 5/5 mg/d) in coronary heart disease (CHD) patients after coronary artery bypass graft (CABG) surgery. Material and methods. The clinical trial included 65 patients (37 men, 28 women aged 45-68 years; mean age 56,3±3,5 years) after CABG. All patients were randomised into two groups: the control group (CG; n=35) and the main group (MG; n=30). Both groups received antiplatelet agents and statins, while the MG patients additionally received Prestance (5/5 mg/d). Prestance therapy started three-four weeks after CABG and lasted for four months. All participants underwent 24-hour monitoring of ECG and blood pressure (BP), Doppler echocardiography, and Doppler ultrasound of brachial and common carotid arteries. Results. Compared to the CG, the MG demonstrated decreased incidence of pain and painless ischemia episodes, reduced maximal ST segment depression and its total duration, and increased rate threshold of myocardial ischemia. In addition, Prestance therapy was associated with improved systolic and diastolic heart function and significantly improved endothelium-dependent vasodilatation. In patients with normal BP, Prestance (5/5 mg/d) did not cause hypotension, but reduced excessive BP variability. In the MG, acute coronary syndrome (ACS) was registered in 1 individual (3,3 %), while in the CG, it was registered in 4 patients (11.4 %), and in 3 cases, coronary artery stenting was performed. Conclusion. In patients with normal BP, Prestance (5/5 mg/d) therapy in the early post-CABG period had a pronounced anti-ischemic, cardio- and vasoprotective effects, and also prevented excessive BP variability.